1999
DOI: 10.1093/carcin/20.11.2131
|View full text |Cite
|
Sign up to set email alerts
|

No association between androgen or vitamin D receptor gene polymorphisms and risk of breast cancer

Abstract: Endogenous hormone exposure is known to alter breast cancer susceptibility and genes responsive to such hormones are plausible candidates for predisposition genes. We have examined polymorphisms in genes for two members of the nuclear receptor superfamily which are expressed in breast tissue and known to moderate rates of cell proliferation in a case-control association study: the androgen receptor (AR) and the vitamin D receptor (VDR). We have used two series of Caucasian female breast cancer cases, one incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 21 publications
2
74
1
2
Order By: Relevance
“…When women from families with breast/ovarian cancer were examined in a case-only analysis, no association was found between (CAG)n repeat length and age at diagnosis or tumor type (Menin et al, 2001). A study of 508 patients and 426 controls from Britain showed no association (Dunning et al, 1999). Overall, we also did not observe any significant association between the CAG repeat polymorphism and BC risk.…”
Section: Discussioncontrasting
confidence: 71%
“…When women from families with breast/ovarian cancer were examined in a case-only analysis, no association was found between (CAG)n repeat length and age at diagnosis or tumor type (Menin et al, 2001). A study of 508 patients and 426 controls from Britain showed no association (Dunning et al, 1999). Overall, we also did not observe any significant association between the CAG repeat polymorphism and BC risk.…”
Section: Discussioncontrasting
confidence: 71%
“…The involvement of BRCA1 protein in steroid hormone regulation 11 combined with the putative role that the polymorphic CAG repeat (encod-ing for a polyglutamine tract) in exon 1 of the AR gene in prostate cancer 12 -14 contributed to the notion that AR gene may be involved in breast cancer pathogenesis. Direct analyses of the CAG repeat number in women diagnosed with breast cancer under 40 15 or 55 years of age, 16 did not demonstrate an association between age at disease diagnosis and CAG repeat size. Recently, a protective effect of having a short AR CAG repeat size allele was shown for Canadian incident breast cancer cases.…”
Section: Introductionmentioning
confidence: 76%
“…The VDR and AR genes are both members of nuclear receptor superfamily regulating the genes for hormone-response (5). The transcriptional activity of the VDR gene is regulated in part by AR gene (6).…”
Section: Introductionmentioning
confidence: 99%